Exploring the Effectiveness of Problem-Based Learning on Mathematical Problem-Solving: A Gender Perspective - Norhaslina, Norhaslina; Oktafia, Mesi; Noperta, Noperta (Journal of Authentic Research on Mathematics Education (JARME), 2025)
One of the essential skills to be developed in mathematics learning is problem-solving ability. The purpose of this study is to analyze the effect of the problem-based learning (PBL) model on students' mathematical problem-solving skills, considering gender aspects (female and male). This experimental study employs a Control Group Posttest Design. Problem-solving ability is used as the dependent variable, the learning model as the independent variable, and gender as the moderating variable. Data collection techniques involve tests consisting of 5 essay questions designed according to Polya's problem-solving indicators. Data analysis is conducted using normality tests, homogeneity tests, and two-way ANOVA tests. The results indicate that the Problem-Based Learning (PBL) model is effective in improving students' mathematical problem-solving skills regardless of gender.